(untitled) (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2023)
INTRODUCTION. Obstructive uropathy (OU) is very prevalent. Its level of bacteremia is high, complicating up to 40% of cases with severe sepsis. OBJECTIVE The purpose of this clinical case report is to describe medical profiles of patients with Obstructive Uropathy at the HCU of Valladolid. MATERIALS AND METHODS All patients of legal age urgently admitted with the diagnosis of UO were included. An observational and descriptive prospective study was designed to classify patients into two groups: severe sepsis patients and non-severe sepsis patients. A descriptive and inferential statistical analysis was carried out, considering a p <0.05 as significant. The quantitative variables were expressed in an interquartile range; medians and the qualitative ones in percentages and absolute numbers. Demographic and clinical data were analysed using Pearson’s Chi-square test (Ӽ2) for categorical variables, and the U - Mann - Whitney test was used for continuous variables. OUTCOMES: Our series consists of 65 patients. UO occurred preferentially in men (63.07%). The most frequent comorbidities were HBP and obesity. In the majority of patients, OU was incomplete and secondary to lithiasis. 64.61% of them developed severe sepsis. The urine culture was positive in 20.63% of the cases, being Escherichia coli the most frequent microorganism. Urinary diversion was urgently performed in 40% of the patients. CONCLUSION: There is an analytical profile characteristic of severe sepsis maintained over time, consisting of an increased percentage of neutrophils and procalcitonin and decreased amount of bicarbonate in the blood